Leveraging community Wi-Fi and spaces for digital health use - Spaulding, Erin M.; Miller, Hailey N.; Metlock, Faith E.; Chepkorir, Joyline; Benjasirisan, Chitchanok; Hladek, Melissa D.; Han, Hae-Ra (Frontiers in Public Health, 2024)
Digital health disparities continue to affect marginalized populations, especially older adults, individuals with low-income, and racial/ethnic minorities, intensifying the challenges these populations face in accessing healthcare. Bridging this digital divide is essential, as digital access and literacy are social determinants of health that can impact digital health use and access to care. This article discusses the potential of leveraging community Wi-Fi and spaces to improve digital access and digital health use, as well as the challenges and opportunities associated with this strategy. The existing limited evidence has shown the possibility of using community Wi-Fi and spaces, such as public libraries, to facilitate telehealth services. However, privacy and security issues from using public Wi-Fi and spaces remain a concern for librarians and healthcare professionals. To advance digital equity, efforts from multilevel stakeholders to improve users’ digital access and literacy and offer tailored technology support in the community are required. Ultimately, leveraging community Wi-Fi and spaces offers a promising avenue to expand digital health accessibility and use, highlighting the critical role of collaborative efforts in overcoming digital health disparities.